Advances of antitumor drug discovery in traditional Chinese medicine and natural active products by using multi‐active components combination - Zhao, Wei; Zheng, Xiao‐Di; Tang, Paula Yun‐Zhi; Li, Hong‐Mei; Liu, Xue; Zhong, Jian‐Jiang; Tang, Ya‐Jie (Medicinal research reviews, 2023)
The antitumor efficacy of Chinese herbal medicines has been widely recognized. Leading compounds such as sterols, glycosides, flavonoids, alkaloids, terpenoids, phenylpropanoids, and polyketides constitute their complex active components. The antitumor monomers derived from Chinese medicine possess an attractive anticancer activity. However, their use was limited by low bioavailability, significant toxicity, and side effects, hindering their clinical applications. Recently, new chemical entities have been designed and synthesized by combining natural drugs with other small drug molecules or active moieties to improve the antitumor activity and selectivity, and reduce side effects. Such a novel conjugated drug that can interact with several vital biological targets in cells may have a more significant or synergistic anticancer activity than a single‐molecule drug. In addition, antitumor conjugates could be obtained by combining pharmacophores containing two or more known drugs or leading compounds. Based on these studies, the new drug research and development could be greatly shortened. This study reviews the research progress of conjugates with antitumor activity based on Chinese herbal medicine. It is expected to serve as a valuable reference to antitumor drug research and clinical application of traditional Chinese medicine.